Determination of impurities in graphite using synchrotron radiation based X-ray fluorescence spectrometry. (October 2017) - Ghosh, M.; Swain, K.K.; Remya Devi, P.S.; Chavan, T.A.; Singh, A.K.; Tiwari, M.K.; Verma, R.
Abstract: Determination of impurities namely Ca, Mn, Fe, Ni, Zn, Sr and Pb in graphite by energy dispersive X-ray fluorescence spectrometry is described using microfocused synchrotron radiation. The internal standard and standard addition methodologies were adopted for quantification and the results were compared with tube-based X-ray fluorescence spectrometry. Analysis of the results by the F and t -tests revealed their statistical equivalence. Synchrotron measurements improved the detection limits by an order of magnitude compared to the tube based technique. Cr and Zr, which were below the quantification limit in tube based technique, were also quantified by synchrotron based technique. Highlights: Trace elements in high purity graphite were determined by SREDXRF. About 10-times improvement in detection limits in SREDXRF compared to tube-based technique. ANOVA and t -test were used for evaluating the statistical variations.